Grammatical Errors In Predicate Verb Usage In Efl Writing: A Systematic Literature Review - Eli Rosiani Limbong; Sara Yusdika Saragih; Raphael Sugara (JURNAL MANAJEMEN PENDIDIKAN, 2026)
Grammatical accuracy remains one of the major challenges encountered by learners of English as a Foreign Language (EFL), particularly in academic writing. Among various grammatical components, predicate verb usage is essential because it determines sentence accuracy, coherence, and the effectiveness of written communication. Although numerous studies have investigated grammatical errors in EFL writing, findings concerning predicate verb errors remain fragmented across different educational contexts. This study, therefore, aims to synthesize existing empirical evidence on predicate verb errors through a Systematic Literature Review (SLR). The review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and analyzed 25 peer-reviewed studies published between 2015 and 2024. Relevant articles were retrieved from Google Scholar, ERIC, and Semantic Scholar using predetermined inclusion and exclusion criteria. The selected studies were analyzed qualitatively to identify the dominant types of predicate verb errors, the underlying factors contributing to these errors, and their pedagogical implications. The findings reveal that subject–verb agreement, tense and aspect, auxiliary verb usage, and verb form selection are the four most frequently reported categories of predicate verb errors, with subject–verb agreement emerging as the most dominant. The review further indicates that these errors are primarily influenced by first-language interference, incomplete mastery of English grammatical rules, and limited exposure to authentic English input. The synthesized evidence suggests that integrating explicit grammar instruction, meaningful writing practice, corrective feedback, and authentic language exposure can substantially improve learners' grammatical competence. This review contributes to the field of EFL writing by providing a comprehensive synthesis of recent empirical evidence and offering practical recommendations for English language teachers, curriculum developers, and future researchers.